EXTENSIVE READING ON ACCURACY, ACCEPTABILITY, AND READABILITY IN TRANSLATION STUDY - Tatik Irawati (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2019)
The purpose of this study was to determine the effect of extensive reading on the ability to translate scientific and non-scientific articles. Translation techniques that often appear a literal translation, adaptation, discursive creation, borrowing, generalization, and calque. Whereas translation methods use a free translation, adaptation, faithful translation, word for word translation. The research method used experimental quantitative with subject 35 in class A and B. The extensive reading value of 25% had the highest score between 81-92, then 45% had average reading ability between 66-80 and 30% low or level the reading is not good with a value of 0-65. Significant between the two is 80% indicating the level of quality of translation results is good if the ER is high.